Real Estate Advertising of Rights, Acts and Legal Facts in Romania - Bancila, Daniel (Acta Universitatis Danubius. Juridica, 2022)
In the specialized legal literature, other important principles have been evoked or are derived from those already shown, among which we mention the principle of the specialty that must indicate the person of the owner, the individualization of the property and the right to which it refers. In a globalized society as we find it today, where economic interests tend to extend beyond the borders of one state or even from one continent to another, after going through a global pandemic that has modified and prequalified the primary needs of the individual as a subject of In fact, opening new doors to possibilities not perceived until recently in many respects, with consequences and implications for real estate markets, freedom of movement, remote work, we find that the purpose of real estate advertising systems, as is the integrated system of cadaster and the land register in Romania, is the one that forms a unitary system, of technical, economic and legal evidence, of national importance, of all real estates on the entire territory of the country, to determine the technical, economic and legal information regarding real estate, to ensure the publicity of real estate rights, personal rights, legal acts and facts, as well as a any other legal relations, through the land book. Also to provide data to public institutions of the state, necessary for the tax system and the real estate market, but also to contribute to ensuring the security of real estate transactions.